Nutritional status of vitamin B12 on small group of dental students based on food frequency questionnaire - Syafiqah, Izzatul; Nur'aeny, Nanan; Herawati, Erna (Universitas Padjadjaran, 2016)
Introduction: Vitamin B12 plays an important role in general cell metabolism. Vitamin B12 also essential for normal hematopoietic, importance in maintaining the integrity of nervous system and formation of nervous system. Even though vitamin B12 is essential for good health, some people may not be getting enough intake of vvitamin B12. The purpose of this research is to get information about the nutritional status of vitamin B12 on dental students based on food frequency questionnaire. Methods: Method used in this research were descriptive non experimental of 30 dental students from Faculty of Dentistry in Universitas Padjadjaran. All samples were given the food frequency questionnaire and recorded the amount of food were taken within 7 days. The consumption of vitamin B12 daily were calculated by using Nutrisurvey software. Results: Among 30 students, there were 7 students who were in lack of consumption of vitamin B12, 14 students or almost half of them who were in normal level and 9 students who were in high level of Vitamin B12 consumption. Conclusion: The Nutritional Status of Vitamin B12 on Small Group of Dental Students Based on Food Frequency Questionnaire were mostly in normal level.